Cases of Domestic Violence Against Women in One Municipality in the Philippines: Input For a Proposed Barangay Action Plan (International Journal of Scientific Research and Management (IJSRM), 2022)
The research aimed to assess the cases of domestic violence against women (VAW) in selected barangays in the Municipality of Santa Cruz, Laguna, Philippines and develop an action plan to enhance the VAW services of the barangays. Descriptive-qualitative research method was employed where documentary analysis and respondent interviews were used to gather data. Permission from concerned agencies and local government units (LGUs) was sought to use and analyze records and other relevant data regarding cases of violence against women. Consent and approval before conducting interview among victims and survivors of violence against women was carefully sought with utmost confidentiality. Results showed that physical abuse of women is the most common recorded case. Other reported cases include psychological abuse, threatening, abandonment of children, child support issues, child custody, and economic abuse. Cases of domestic violence against women occurred because of perpetrator’s dependence on illegal drugs, jealousy and the presence of third party in their relationship, perpetrator’s influence of alcohol, unemployment and provocation of the intimate partner. Barangay respondents provide services in addressing VAW in compliance with the Magna Carta of Women and R.A. 9262. Certain conditions and challenges regarding VAW services of barangay were observed during the conduct of this study.